Recircumscription of the genera Goniozus and Sierola (Hymenoptera: Bethylidae) based on morphological and molecular evidence - Magnacca, Karl N. (Zootaxa, 2024)
A number of undescribed species of the bethylid genera Goniozus and Sierola have been discovered in Australia and North America with character states that had previously been thought to be exclusive to one or the other, prompting a re-examination of the generic boundaries. Analysis of a large dataset of cytochrome oxidase I mtDNA sequences and key morphological characters found that Goniozus is well defined by two insertion-deletion events in COI. The traditional morphological characters can also be used to separate the genera, but variation within the regional fauna must be taken into account. Sierola always has four maxillary palpomeres; Goniozus usually has five, but some Nearctic species have four. Goniozus always has cell 2R1 of the fore wing open, with vein Rs weakly curved; Sierola has Rs bent sharply towards the wing margin, usually closing 2R1, but a small number of recently-described Hawaiian species and many undescribed Australian species and have it narrowly to moderately open. As a result of these changes, two species are transferred from Goniozus to Sierola: Sierola angulata (Muesebeck, 1933) comb. nov. from Australia, and Sierola jamiei (Ward, 2013) comb. nov. from New Zealand.